The Role of Green Manufacturing and Energy Management System in the Implementation of Carbon Emission Disclosure and its Impact on Company Performance in the Power Generation Sector in Serang Regency - Ahmad Adrian Hanafiyah; Tata Rustandi; Udin Suadma; Kenedi (Postgraduate, University of Mataram, 2024)
This study focuses on Steam Power Plant companies (PLTU) in Serang Regency (Suralaya Power Plant, Jawa 7 Power Plant, and Merak Energi Indonesia Power Plant). It investigates the impact of sustainable strategies, specifically energy management and carbon emission disclosure, on company performance. The data was obtained by distributing questionnaires to 270 respondents, which were subsequently analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach. The direct analysis shows that green manufacturing not significantly affect company performance, conversely, energy management significantly improves company performance, green manufacturing significantly influences carbon emission disclosure. Energy management also contributes to higher carbon emission disclosure, and carbon emission disclosure positively affects company performance, emphasizing the benefits of transparency for stakeholder trust and operational efficiency. Indirect effects reveal that green manufacturing and energy management positively impact company performance through carbon emission disclosure. This research offers insights for PLTU companies in Serang Regency. Sustainable strategies focusing on energy management and carbon emission disclosure enhance company performance and transparency. Further investigation is needed to understand complex relationships, considering external factors and specific management practices. These findings provide significant insights but are part of the broader puzzle in achieving sustainable business practices and superior performance.